Coding theory introduction - van Lint, J. H. (IEEE transactions on information theory, 1988)
THERE ARE fourteen papers on algebraic and combinatorial coding theory in this special issue. Their subject matter mix attests that there are at least two hot topics currently, namely, covering radius problems (four papers) and algebraic geometric codes (three papers); moreover, several other papers on these two areas are in the pipeline. Of course, there are also a few papers on decoding algorithms.